Mike Leigh on Mike Leigh - Leigh, Mike 1943- (Faber and Faber, 2008)
Five-time Oscar nominee and BAFTA winner, Mike Leigh is one of the world cinema's pre-eminent figures. Now, in this definitive career-length interview, he reflects on all that has gone into the making of his unique body of work.
Bleak Moments -- Hard labour -- The permissive society -- "The five-minute films" -- Nuts in may -- The kiss of death -- Abigail's party -- Who's who -- Grown-ups -- Home sweet home -- Meantime -- Four days in july -- The short and curlies -- High hopes -- Life is sweet -- A sense of history -- Naked -- Secrets & lies -- Career Girls -- Topsy-Turvy -- All or nothing -- Vera Drake
Keywords: Leigh, Mike <1943-> -- Interviews; Leigh, Mike -- 1943-; Interview